Penilaian Aktiva Hayati - Wening, Endang Sri (Universitas Muhammadiyah Yogyakarta, Indonesia, 2001)
Wood stands and animals are still alive is the company's assets that are sometimes not rated by the company, as well as the value added created because of growth, are also not recognized by the company. Whereas information concerning the value of biological assets (animals and plants) is a very important information to estimate the cash flows that may be obtained. In its assessment used biological fair value of assets owned by the company. This article aims to provide an overview of how to assess the biological assets owned by the companies of agriculture so that the company can estimate the cash flows that would be obtained.Â Â Â